2003
DOI: 10.1080/0020739031000148930
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of undergraduate core material in the light of hand-held computer algebra systems

Abstract: This study investigates how hand-held computer algebra systems may be used to complete undergraduate mathematics course work tasks. Core university mathematics courses are examined in detail using a question classification scheme that describes the style of a question, rather than the syllabus topic. The majority of the tasks examined could be completed directly using the device. Surreptitious use of the hand-held device would subvert the intentions of the course designer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 6 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…Indeed, several studies have shown that students are mainly given tasks that promote the use of predetermined algorithms, procedures, and/or examples of how to solve the task rather than opportunities to engage in a problem-solving struggle without instruction (Stacey and Vincent, 2009;Denisse et al, 2012;Boesen et al, 2014;Jäder et al, 2019). For example, Jäder et al (2019) examined mathematics textbooks from 12 countries and found that 79% of the textbook tasks could be solved by merely following provided procedures, 13% could be solved by minor adjustments of the procedure, and only 9% required students to create (parts of) their own methods (for similar findings, also see Pointon and Sangwin, 2003;Bergqvist, 2007;Mac an Bhaird et al, 2017). In response to these findings, Lithner (2008Lithner ( , 2017 developed a framework arguing that the use of instructions in terms of predefined algorithms has negative long-term consequences for the development of students' conceptual understanding.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, several studies have shown that students are mainly given tasks that promote the use of predetermined algorithms, procedures, and/or examples of how to solve the task rather than opportunities to engage in a problem-solving struggle without instruction (Stacey and Vincent, 2009;Denisse et al, 2012;Boesen et al, 2014;Jäder et al, 2019). For example, Jäder et al (2019) examined mathematics textbooks from 12 countries and found that 79% of the textbook tasks could be solved by merely following provided procedures, 13% could be solved by minor adjustments of the procedure, and only 9% required students to create (parts of) their own methods (for similar findings, also see Pointon and Sangwin, 2003;Bergqvist, 2007;Mac an Bhaird et al, 2017). In response to these findings, Lithner (2008Lithner ( , 2017 developed a framework arguing that the use of instructions in terms of predefined algorithms has negative long-term consequences for the development of students' conceptual understanding.…”
Section: Introductionmentioning
confidence: 89%
“…The MATH taxonomy classifies tasks according to the skills needed to solve them, with various categories arranged in three broad groups; these are summarised in Table 1. A similar classification scheme was later developed independently by Pointon & Sangwin (2003) and by Tallman et al (2016). The similarity of these taxonomies supports the validity of the approach.…”
Section: Taxonomiesmentioning
confidence: 57%
“…The impact of technology on the style of examination questions has been discussed in detail by authors such as Brown (2001), Drijvers (1998), Kokol-Voljc (1999 and Pointon and Sangwin (2003). However, the focus of these authors was on the impact that the graphics calculator had on the style of the questions, whereas the analysis detailed in this paper is focussed on the impact that the graphics calculator has had on the type of mathematics skills assessed.…”
Section: Literature Reviewmentioning
confidence: 95%